INSTRUCTIONAL MEDIA IN TEACHING ENGLISH TO YOUNG LEARNERS: A CASE STUDY IN ELEMENTARY SCHOOLS IN KUNINGAN - Wildan Nurul Aini (Journal of English and Education, 2013)
This research investigated (1) the use of instructional media by the teachers in teaching English to young learners; (2) the problems that they encounter in using instructional media; also (3) problem solving of the media utilization challenges. This study was conducted in elementary schools in Kuningan. To collect the data, the researcher employed observation and interview techniques. The result of the study indicates that there are five types of instructional media which are generally used by the teachers, comprising: (1) boards; (2) realia; (3) pictures; and (4) books. Each of them is used in various ways. The teachers faced challenges in both process of selecting and using instructional media. The strategy used to solve the problems during selection process was utilizing available media. Meanwhile, to overcome the problem during the use of instructional media were by requesting technician help, borrowing instructional media supply from other class and preparing back-up instructional media. Keywords:Instructional media, media utilization, media selection, problem solving of media utilization challenges, young learners